2005
DOI: 10.1111/j.1532-5415.2005.53114.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Management in Elderly Patients: Correlation Between Adherence to Treatment Guidelines and Patient Satisfaction

Abstract: Pain in elderly surgical patients remains undermanaged. Simple strategies such as emphasizing preoperative education may have a large effect in pain management. This study developed a validated patient satisfaction score and a MR instrument to assist in monitoring pain management quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 28 publications
(43 reference statements)
3
34
1
4
Order By: Relevance
“…Similarly, patients asked for their weekly handouts to have more information on them. These findings are consistent with prior literature suggesting that the amount of education learned [6,12] and the practice setting (i.e., organization model) [28] are directly related to patient satisfaction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, patients asked for their weekly handouts to have more information on them. These findings are consistent with prior literature suggesting that the amount of education learned [6,12] and the practice setting (i.e., organization model) [28] are directly related to patient satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…Past research has also found that minorities report higher pain levels than Caucasians and resultantly, individuals with higher average daily pain reported using more CAM [26]. Collectively, these results are consistent with past findings that suggest patients are not fully aware of available pain relief options [12] and are open to alternative treatment options. The VA healthcare system has moved toward making certain CAM treatment options available as research supports their utility and reveals what options veterans are willing to try [27].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The use of peri-operative analgesia protocols is recommended, and improves patient satisfaction [72], but must be individualised for each patient, to take into account, for example, his/her chronic pain status, frailty, pain assessment, concurrent medication, renal function and cognitive impairment [73,74]. Multimodal analgesia is not restricted to pharmacological agents, and may involve, for example, postural support, pressure care and patient warming.…”
Section: Pain Managementmentioning
confidence: 99%